2018
DOI: 10.4103/jpgm.jpgm_219_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association of bone morphogenetic protein 4-V152A and SIX homeobox 6-H141N polymorphisms with congenital cataract and microphthalmia in Western Indian population

Abstract: Background:Congenital cataract and microphthalmia are highly heterogeneous congenital eye disorders that affect normal vision. Although mutation in several genes has been shown to cause congenital cataract and microphthalmia, genetic studies associating single-nucleotide polymorphisms with these conditions is scarce. Hence, the present study aims to investigate the association of bone morphogenetic protein 4 (BMP4)-V152A (rs17563), and SIX homeobox 6 (SIX6)-H141N (rs33912345) polymorphisms with congenital cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Even if the intronic SNP does not have a functional consequence, it may exist in linkage disequilibrium with other functional SNPs and thereby help recognize the disease loci. Considering the potential association of SNPs with congenital cataract and the dearth of information on genetic association studies using intronic SNPs,[ 38 39 ] the present study was performed to understand the distribution of intronic SNPs rs3788059 ( CRYAA ), rs2070894 ( CRYAB ), rs2071861 ( CRYBA4 ), rs5752083 ( CRYBB2 ), and rs5996863 ( CRYBB2 ) in congenital cataracts and normal healthy controls. Although association studies using these markers have never been reported in congenital cataracts, studies on rs2070894 concerning colorectal and oral cancer[ 40 41 ] and rs2071861 concerning high myopia[ 42 43 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the intronic SNP does not have a functional consequence, it may exist in linkage disequilibrium with other functional SNPs and thereby help recognize the disease loci. Considering the potential association of SNPs with congenital cataract and the dearth of information on genetic association studies using intronic SNPs,[ 38 39 ] the present study was performed to understand the distribution of intronic SNPs rs3788059 ( CRYAA ), rs2070894 ( CRYAB ), rs2071861 ( CRYBA4 ), rs5752083 ( CRYBB2 ), and rs5996863 ( CRYBB2 ) in congenital cataracts and normal healthy controls. Although association studies using these markers have never been reported in congenital cataracts, studies on rs2070894 concerning colorectal and oral cancer[ 40 41 ] and rs2071861 concerning high myopia[ 42 43 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%